2009
DOI: 10.1088/0004-637x/698/2/2087
|View full text |Cite
|
Sign up to set email alerts
|

Proto-Planetary Disk Chemistry Recorded by D-Rich Organic Radicals in Carbonaceous Chondrites

Abstract: Insoluble organic matter (IOM) in primitive carbonaceous meteorites has preserved its chemical composition and isotopic heterogeneity since the solar system formed ∼4.567 billion years ago. We have identified the carrier moieties of isotopically anomalous hydrogen in IOM isolated from the Orgueil carbonaceous chondrite. Data from high spatial resolution, quantitative isotopic NanoSIMS mapping of Orgueil IOM combined with data from electron paramagnetic resonance spectroscopy reveals that organic radicals hold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
109
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(120 citation statements)
references
References 44 publications
8
109
3
Order By: Relevance
“…No D-rich hot spots are observed in IOM of heated chondrites, i.e. CO, CV [60] pointing out to their thermal sensitivity. The distribution of the deuterium has also been studied at the molecular scale [61,62].…”
Section: Water In Chondritesmentioning
confidence: 91%
See 1 more Smart Citation
“…No D-rich hot spots are observed in IOM of heated chondrites, i.e. CO, CV [60] pointing out to their thermal sensitivity. The distribution of the deuterium has also been studied at the molecular scale [61,62].…”
Section: Water In Chondritesmentioning
confidence: 91%
“…It must be EPOV 2012 03001-p. 5 noted that the lowest isotopic enrichment was measured in Abee enstatite chondrite (δD = -480 ‰; D/H = 80×10 -6 ) [56,57]. Isotopic imaging has revealed that H isotopes can exhibit large variations in the IOM of CI, CM and CR chondrites with the occurrence of D-rich " hot spots": micron sized areas with large positive D anomalies (figure 3), which could go up to δD = 8000 ‰ (D/H=1402×10 -6 ; [58][59][60]). No D-rich hot spots are observed in IOM of heated chondrites, i.e.…”
Section: Water In Chondritesmentioning
confidence: 99%
“…No D-rich hot spots are observed in IOM of heated chondrites, i.e. CO, CV (Remusat et al 2009) pointing out to their thermal sensitivity.…”
Section: D/h Ratio Heterogeneities In the Iommentioning
confidence: 93%
“…Busemann et al 2006;Nakamura-Messenger et al 2006;Remusat et al 2009). No D-rich hot spots are observed in IOM of heated chondrites, i.e.…”
Section: D/h Ratio Heterogeneities In the Iommentioning
confidence: 97%
See 1 more Smart Citation